RENT-SEEKING TOWARDS ECONOMIC GROWTH: EMPIRICAL STUDY IN LOWER-MIDDLE-INCOME COUNTRIES - Laut, Lorentino; Febrianti, Erika; Sugiharti, Retno (TRIKONOMIKA, 2023)
The good effects of globalization are not felt by all countries. Lower-middle-income countries are constrained by ineffective or poorly implemented economic policies in those countries. One indicator of this ineffectiveness is the low rate of controlling rent-seeking in lower-middle-income countries. Therefore, this study analyzes the effect of controlling rent-seeking on the economic growth of lower-middle-income countries. It is important to study where economic growth has an important role in the economic development of lower-middle-income countries. This study also uses control variables such as capital formation, population, and lag of economic growth through the Partial Adjustment Model (PAM) approach. Based on the results of regression testing that has been carried out, controlling rent seeking and capital formation is known to have a positive and significant effect on economic growth in lower-middle-income countries. Meanwhile population has a negative and significant effect on the economic growth of lower-middle-income countries.